PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING DENGAN MEMANFAATKAN LINGKUNGAN SEKOLAH TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS II SD NEGERI 7 KAYUAGUNG (JS (JURNAL SEKOLAH), 2022)
Abstract: The learning process in schools has a close relationship between teachers, students, curriculum, facilities and infrastructure, a teacher must be able to choose the right learning strategy according to the material to be delivered in the learning process. One approach that can be applied is the contextual teaching and learning approach, which means an approach that connects each learning material with the environment around the child so that children do not get bored quickly in participating in learning. A conducive school environment is also a driving factor that can provide a special attraction for students during the learning process, and conversely a less pleasant school environment will cause boredom and boredom. The research method used in this study is experimental research, namely research methods based on the philosophy of positivism, used to examine certain populations or samples, data collection using test instruments, data analysis is statistical, this research is to measure student learning outcomes, meaning the abilities possessed students after they receive their learning experienc. The results of the calculation of the hypothesis test show that the significant value